Hedging of the European option with nonsmooth payment function - Glonti, O. A.; Purtukhiya, O. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider onе type of European option in the case of the Black – Scholes financial market model whose payment functionis a certain combination of binary and Asian options. The corresponding hedging scheme is analyzed.We deduce the formulafor the Clark stochastic integral representation of the corresponding Wiener functional with integrand represented in theexplicit form.